FORMULASI GEL ANTIINFLAMASI SEDIAAN EKSTRAK DAUN KUBIS (BRASSICA OLERACEA VAR. CAPITATA) UNTUK MENGURANGI PEMBENGKAKAN PAYUDARA PASCAPERSALINAN - A'yun, Qurratul; Rahman, Alief Putriana; Alrosyidi, Ach. Faruk (Yayasan Nusantara Hasana Berdikari, 2025)
Cabbage leaves (Brassica oleracea var. capitata) are known to have potential anti-inflammatory activity so they can be used as therapy to reduce swelling, especially in postpartum mothers. Its main active ingredients are flavonoids and phenolics, which play a role in inhibiting the inflammatory process This study aims to develop a gel based on cabbage leaf extract as a safe and effective topical preparation to treat postpartum swelling. The research was conducted using an experimental method using female mice as a test animal model. Cabbage leaf extract was obtained through the maceration method with a 96% ethanol solvent, which was then formulated into a gel with three variations in extract concentration (2.5%, 5%, and 7.5%). Evaluation included preparation quality tests (organoleptics, homogeneity, pH, viscosity, and dispersibility) as well as anti-inflammatory tests using carrageenan edema models. Results showed that all gel formulas met the quality criteria of the preparation with an appropriate pH for optimal skin application and spread. Anti-inflammatory tests showed that the formula with a 5% extract concentration had the best activity, with a significant decrease in the volume of edema in mice compared to positive and negative controls. In addition, the viscosity and dispersibility of the gel are in accordance with the standards of topical preparations. In conclusion, cabbage leaf extract gel has the potential to be a safe and effective anti-inflammatory pharmaceutical preparation for clinical applications, particularly in reducing postpartum swelling. This research contributes to the development of natural ingredients-based drugs with wide use prospects in the field of maternal health.